Strengthening the Resilience of Objective-Oriented Health System Reforms. Analysis of the Left-Turn in the Health Reform Proposals in Mexico (2019) and Colombia (2023) - Laura Flamand; Octavio Gómez-Dantés; Natalia Losada-Trujillo; Diana Pinto; Edson Serván-Mori; Diego Cerecero-García; Thomas Hone; Sumit Mazumdar (Health Systems & Reform)
This article explores the political and institutional factors that led two leftist governments to propose sweeping, rather than incremental, changes to earlier objective-oriented health systems reforms. One is the government of Mexico led by President Andrés Manuel López Obrador, who in 2019 proposed to replace reforms approved in 2003. His proposal was passed by Congress and implemented. The other is the government of President Gustavo Petro in Colombia, who in 2023 recommended the replacement of the health reform implemented in Colombia since 1993. His proposal was rejected by Congress. Drawing on historical institutionalism, we analyzed the interactions among actors and institutions that shaped their reform proposals, focusing on policy feedback effects and veto points. We examined news articles, government and policy documents, electoral results, presidential approval ratings, and legislative voting records. We also conducted in-depth interviews with key actors about the factors behind the need for reform, the policy proposals, and the public and legislative debates. In both countries, we found that a combination of policy feedback effects (political ideology beliefs, and policy legacies that shape public perceptions and expectations) and veto points (the perceived strength of the president vis-à-vis reform opponents) help explain the decisions to propose such significant changes to the health care systems. Based on these findings, we offer initial recommendations for safeguarding objective-oriented health system reforms in lower-middle and upper-middle-income countries facing stark political change, especially in polarized contexts. Objective-oriented health system reforms should be evidence-based and supported by long-term financing, delivery, management, and evaluation plans. For long-term resilience, they also need multiple networks to secure them, including citizens well informed about their benefits, health workers with a sense of ownership, and legal protections.